Preparation method of biomass hard carbon sodium ion battery negative electrode material with good consistency

By using the synergistic effect of acid liquid, crosslinking agent and organic pore-forming agent in the biomass hard carbon material, a uniformly distributed modified raw material is formed and carbonized, the problem of low specific capacity of sodium ion battery hard carbon negative electrode material is solved, and the preparation of biomass hard carbon sodium ion battery negative electrode material with high consistency and high sodium storage capacity is achieved.

CN119735196AActive Publication Date: 2025-04-01SHENZHEN JANAENERGY TECH CO LTD

Patent Information

Application Number
CN202411956675.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-01
Estimated Expiration
2044-12-29

AI Technical Summary

Technical Problem

The energy density of sodium ion batteries is low, mainly due to the lower specific capacity of hard carbon negative electrode materials. The inorganic salt pore-forming agent used in the prior art leads to a small number of micropores, poor consistency, and inevitably introduce mesopores and macropores.

Method used

By wet mixing the biomass raw materials with acid liquid, crosslinking agent and organic pore-forming agent, centrifugation, washing and drying after temperature control reaction, a modified raw materials rich in organic pore-forming agent were obtained, and pre-carbonization and high-temperature carbonization were performed under a protective atmosphere to form a biomass hard carbon sodium ion battery negative electrode material with good consistency.

Benefits of technology

The formation of a rich microporous structure inside the hard carbon material is achieved, the sodium storage capacity is improved, the consistency of the material is ensured, the specific surface area is reduced, and the first week efficiency is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a biomass hard carbon sodium ion battery negative electrode material preparation method, which comprises: S1, raw material pre-crushing treatment: crushing and screening a raw material to obtain a biomass raw material with a first fineness; s2, raw material homogenization modification: performing wet mixing on the biomass raw material obtained in the step S1, an acid solution, a cross-linking agent and an organic pore-forming agent, performing temperature control reaction, centrifuging, washing and drying to obtain a modified raw material which is uniformly distributed and rich in the organic pore-forming agent; s3, pre-carbonization treatment: pre-carbonizing the modified raw material obtained in the step S2 in a protective atmosphere to obtain a pre-carbonized material; s4, crushing and refining: crushing and refining the pre-carbonized material obtained in the step S3 to obtain a pre-carbonized material with second fineness; and S5, performing high-temperature carbonization: performing high-temperature carbonization on the pre-carbonized material obtained in the step S4 in a protective atmosphere to obtain the final hard carbon sodium-ion battery negative electrode material. The method has the characteristics of good consistency, high first-week efficiency and effective improvement of sodium storage capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency. Background Art

[0002] Compared with the mainstream lithium-ion batteries on the market, sodium-ion batteries have the advantages of low production cost, good rate performance, good low-temperature performance, and high safety performance. They have good development prospects in the fields of energy storage, start-stop power supply, and two-wheeled electric vehicles. However, the low energy density of sodium-ion batteries limits their further development.

[0003] One of the reasons for the low energy density of sodium-ion batteries is the low specific capacity of hard carbon negative electrode materials. The mainstream raw materials of hard carbon materials include biomass, coal, asphalt and organic polymer materials, among which biomass raw materials have the advantages of wide sources, low cost, simple processing technology and sufficient supply, and are currently the mainstream choice of hard carbon negative electrode manufacturers.

[0004] Constructing a microporous structure inside hard carbon materials is an effective way to increase their sodium storage capacity. Currently, the industry mainly adds pore-forming agents to raw materials or intermediates, and then activates them during the subsequent carbonization process to generate rich pore structures in carbon materials.

[0005] In the prior art, inorganic salts such as NaOH, KOH, and ZnCl2 are mainly used as pore formers. However, the crystallite size of such pore formers in the raw materials is large and unevenly distributed, so the number of micropores generated is small, the consistency is poor, and mesopores and macropores are inevitably introduced, the pore-forming specific surface area is too large, and the capacity improvement is extremely limited. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, which has the characteristics of good consistency, high first-week efficiency and effectively improved sodium storage capacity.

[0007] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crushing and sieving the raw material to obtain a biomass raw material of the first fineness; S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet-mixed with acid solution, cross-linking agent and organic pore-forming agent, centrifuged, washed and dried after temperature-controlled reaction to obtain a modified raw material rich in organic pore-forming agent evenly distributed; S3, pre-carbonization treatment: pre-carbonizing the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material; S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness; S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material.

[0008] In step S2 of the present invention, at the beginning of the reaction, the highly ordered dense structure inside the biomass is opened. Specifically, biomass is mainly composed of cellulose, hemicellulose and lignin, of which cellulose accounts for the highest proportion, about 40% to 50%. Its chain structure is regular, and the hydroxyl groups on the molecular chain form a strong hydrogen bond network between different celluloses, resulting in a close molecular arrangement between cellulose fibers, and it is difficult for the pore-forming agent to penetrate into the interior of the biomass material. Under the action of the acid solution, the charge state of the -OH group inside the cellulose is changed, thereby destroying the hydrogen bond, weakening the binding force between the cellulose molecules, and opening the structure. Under the catalytic action of the acid, the cross-linking agent undergoes a cross-linking reaction between molecules, transforming from a small molecule organic matter into a polymer with a larger molecular weight; at the same time, a molecular-level reaction occurs between the cross-linking agent and the -OH group of cellulose, achieving the purpose of uniform dispersion in the biomass raw material; in addition, the organic pore-forming agent has a good affinity with the cross-linking agent, so that the organic pore-forming agent is also uniformly distributed in the biomass raw material.

[0009] Further, in step S2, the reaction temperature is 60-200°C, and the reaction time is 3-10h.

[0010] Further, in step S2, the acid solution is one or more of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, formic acid, acetic acid, citric acid, oxalic acid and benzoic acid; the amount of the acid solution is 0.5-10 wt.% of the amount of biomass raw material added. In the present invention, the amount of acid added affects the effect of the present invention: specifically, if the amount of acid added is too low, the dense structure of the biomass raw material cannot be fully opened, and the purpose of the present invention cannot be achieved; if the amount of acid added is too high, cellulose will be dissolved in the acid solution, resulting in a decrease in product yield, which is not conducive to actual production.

[0011] Further, in step S2, the crosslinking agent is one or more of polyethylene glycol, phthalic acid glycosides, malonic acid, formaldehyde, benzaldehyde, propylenediamine, glyoxal, terephthalaldehyde, urea-formaldehyde, furfural, diaminodiphenylmethane, m-xyleneamine, and diphenyl diammonium; the amount of the crosslinking agent added is 1-5wt.% of the amount of the biomass raw material added. Specifically, in the present invention, the crosslinking agent is an organic reagent containing hydroxyl, anhydride, aldehyde, carboxyl, and amino functional groups and is easily soluble in water. The amount of the crosslinking agent added affects the final technical effect. If the amount of the crosslinking agent added is too low, the crosslinking functional groups are insufficient, and the purpose of uniformly dispersing the pore-forming agent in the biomass raw material cannot be achieved; if the amount of the crosslinking agent added is too high, the production cost of the material is pushed up, which is not conducive to actual production.

[0012] Further, in step S2, the organic pore-forming agent is one or more of sodium gluconate, potassium gluconate, magnesium gluconate, zinc gluconate, sodium acetate, potassium acetate, zinc acetate, magnesium acetate, sodium citrate, potassium citrate, zinc citrate, magnesium citrate, sodium oxalate, potassium oxalate, zinc oxalate, magnesium oxalate, sodium formate, potassium formate, zinc formate, magnesium formate, sodium benzoate, potassium benzoate, zinc benzoate, and magnesium benzoate; the amount of the organic pore-forming agent added is 5-50wt.% of the amount of the biomass raw material added. If the amount of the organic pore-forming agent added is too low, a rich microporous structure cannot be formed inside the hard carbon material, and the capacity improvement is limited; if the amount of the organic pore-forming agent added is too high, mesopores and macropores are easily formed in the hard carbon material, which has an adverse effect on its electrochemical performance.

[0013] Furthermore, in step S3, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 500-1000°C, and the carbonization time is 2-6h. During the carbonization process, the organic pore former is pyrolyzed at high temperature to form metal oxides, and then the metal oxides act as activators to activate the carbon layer to form a porous structure. In the present invention, the carbonization temperature and carbonization time affect the effect of the present invention: if the carbonization temperature is too low or the time is insufficient, the activation effect is not obvious, and a rich microporous structure cannot be formed inside the carbon material; on the contrary, the activation effect is too strong, and the carbon material continues to be activated after the micropores are activated, and finally a mesoporous or macroporous structure is formed, resulting in insufficient micropores in the hard carbon material and excessive specific surface area.

[0014] Further, in step S4, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 1200-1500°C, the carbonization time is 2-8h, and the heating rate is 1-15°C / min. Higher carbonization temperature, longer carbonization time, and slower heating rate are conducive to the graphitization of carbon materials, promote the collapse of open micropore walls to form closed internal pores, and reduce the specific surface area of ​​the material. However, excessively high carbonization temperature will lead to excessive graphitization of the material and narrow interlayer spacing, which is not conducive to the deintercalation of sodium ions between carbon layers and affects the rate performance of carbon materials; excessively long carbonization time and too slow heating rate will increase the production cycle of the product, increase production costs, and are not conducive to actual production.

[0015] Furthermore, in step S1, the mesh number of the sieve is ≥15 meshes; if the mesh number of the sieve is too small, the particle size of the obtained biomass material is too large, which is not conducive to the occurrence of the modification reaction.

[0016] Furthermore, in step S4, the pulverizing method is one or more of roller mill, mechanical mill, Raymond mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the carbonized material is pulverized until its D50 is 3-15 μm.

[0017] Furthermore, in step S1, the raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, corn cob, straw, reed, bamboo, rice husk, poplar, eucalyptus, pine, bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

[0018] The present invention provides a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, which has the following beneficial effects: First, good consistency. The cross-linking agent makes the organic pore-forming agent evenly distributed in the raw material, so the product shows good consistency; Second, the first-cycle efficiency is high. The synergistic effect of acid, cross-linking agent and organic pore-forming agent forms a rich microporous structure inside the hard carbon material, and almost no mesopores and macropores are generated. In the subsequent high-temperature sintering process, the micropores are closed, so that the material has a lower specific surface area and exhibits a lower first-cycle efficiency. Third, the sodium storage capacity is effectively improved. The dense structure of biomass is opened by acid catalysis, so that the activator can fully penetrate into the biomass raw material; the organic cross-linking agent makes the pore-forming agent evenly distributed inside the biomass raw material. The synergistic effect of acid, cross-linking agent and organic pore-forming agent forms a rich microporous structure inside the hard carbon material. The microporous structure serves as a sodium storage active site to increase the sodium storage capacity of the hard carbon material. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0020] The present invention discloses a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crushing and sieving the raw material to obtain a biomass raw material of the first fineness; S2. Raw material homogenization modification: wet-mix the biomass raw material obtained in step S1 with acid solution, cross-linking agent and organic pore-forming agent, centrifuge, wash and dry after temperature-controlled reaction to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed; S3, pre-carbonization treatment: pre-carbonizing the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material; S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness; S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material.

[0021] Further, in step S2, the reaction temperature is 60-200°C, and the reaction time is 3-10h.

[0022] Furthermore, in step S2, the acid solution is one or more of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, formic acid, acetic acid, citric acid, oxalic acid and benzoic acid; the amount of the acid solution is 0.5-10 wt.% of the amount of biomass raw material added.

[0023] Furthermore, in step S2, the cross-linking agent is one or more of polyethylene glycol, phthalic acid glycosides, malonic acid, formaldehyde, benzaldehyde, propylenediamine, glyoxal, terephthalaldehyde, urea-formaldehyde, furfural, diaminodiphenylmethane, m-xyleneamine, and diammonium biphenyl; the amount of the cross-linking agent added is 1-5wt.% of the amount of biomass raw material added.

[0024] Further, in step S2, the organic pore-forming agent is one or more of sodium gluconate, potassium gluconate, magnesium gluconate, zinc gluconate, sodium acetate, potassium acetate, zinc acetate, magnesium acetate, sodium citrate, potassium citrate, zinc citrate, magnesium citrate, sodium oxalate, potassium oxalate, zinc oxalate, magnesium oxalate, sodium formate, potassium formate, zinc formate, magnesium formate, sodium benzoate, potassium benzoate, zinc benzoate, and magnesium benzoate; the amount of the organic pore-forming agent added is 5-50wt.% of the amount of biomass raw material added.

[0025] Furthermore, in step S3, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 500-1000° C., and the carbonization time is 2-6 hours.

[0026] Further, in step S4, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 1200-1500° C., the carbonization time is 2-8 hours, and the heating rate is 1-15° C. / min.

[0027] Furthermore, in step S1, the mesh number of the sieve is ≥15 meshes.

[0028] Furthermore, in step S4, the pulverizing method is one or more of roller mill, mechanical mill, Raymond mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the carbonized material is pulverized until its D50 is 3-15 μm.

[0029] Furthermore, in step S1, the raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, corn cob, straw, reed, bamboo, rice husk, poplar, eucalyptus, pine, bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak. Example

[0030] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crushing and sieving the raw material to obtain a biomass raw material of the first fineness. Specifically, the mesh number of the sieve is ≥15 meshes, and the raw material is coconut shell, walnut shell, or nut shell.

[0031] S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet mixed with acid solution, cross-linking agent, and organic pore-forming agent, centrifuged, washed, and dried after temperature-controlled reaction to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. Specifically, the reaction temperature is 200°C, the reaction time is 6h; the acid solution is hydrochloric acid, and the amount of acid solution is 0.5wt.% of the amount of biomass raw material added; the cross-linking agent is polyethylene glycol and phthalic acid glycoside, and the amount of cross-linking agent added is 5wt.% of the amount of biomass raw material added; the organic pore-forming agent is sodium gluconate, potassium gluconate, magnesium gluconate, and zinc gluconate, and the amount of organic pore-forming agent added is 25 wt.% of the amount of biomass raw material added.

[0032] S3, pre-carbonization treatment: pre-carbonize the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 1000° C., and the carbonization time is 4 hours.

[0033] S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness. Specifically, the protective atmosphere is nitrogen, the carbonization temperature is 1500°C, the carbonization time is 5h, and the heating rate is 1°C / min; the crushing method is a double roller, a mechanical mill, or a Raymond mill, and the carbonized material is crushed to a D50 of 3-15μm.

[0034] S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material. Example

[0035] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crushing and sieving the raw materials to obtain biomass raw materials of the first fineness. Specifically, the mesh number of the sieve is ≥15 meshes, and the raw materials are sugarcane bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

[0036] S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet mixed with acid solution, crosslinking agent, and organic pore-forming agent, and the reaction is centrifuged, washed, and dried after temperature control to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. Specifically, the reaction temperature is 120°C, and the reaction time is 3h; the acid solution is acetic acid, citric acid, oxalic acid, and benzoic acid, and the amount of acid solution is 10 wt.% of the amount of biomass raw material added; the crosslinking agent is meta-xylene ammonia and diphenyl diammonium, and the amount of crosslinking agent added is 3wt.% of the amount of biomass raw material added; the organic pore-forming agent is zinc formate, magnesium formate, sodium benzoate, potassium benzoate, zinc benzoate, and magnesium benzoate, and the amount of organic pore-forming agent added is 5wt.% of the amount of biomass raw material added.

[0037] S3, pre-carbonization treatment: pre-carbonize the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen, the carbonization temperature is 800° C., and the carbonization time is 2 hours.

[0038] S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness. Specifically, the protective atmosphere is argon, the carbonization temperature is 1400°C, the carbonization time is 2h, and the heating rate is 15°C / min; the crushing method is ball milling and sand milling, and the carbonized material is crushed to a D50 of 3-15μm.

[0039] S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material. Example

[0040] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crush and sieve the raw material to obtain a biomass raw material of the first fineness. Specifically, the mesh number of the sieve is ≥15 meshes, and the raw material is coconut shell, walnut shell, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

[0041] S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet mixed with acid solution, cross-linking agent, and organic pore-forming agent, and the reaction is centrifuged, washed, and dried after temperature control to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. Specifically, the reaction temperature is 60°C, and the reaction time is 10h; the acid solution is hydrochloric acid, nitric acid, oxalic acid, and benzoic acid, and the amount of acid solution is 5wt.% of the amount of biomass raw material added; the cross-linking agent is polyethylene glycol, phthalic acid glycoside, malonic acid, and diphenyl diammonium, and the amount of cross-linking agent added is 3wt.% of the amount of biomass raw material added; the organic pore-forming agent is sodium gluconate, potassium gluconate, magnesium gluconate, magnesium oxalate, sodium formate, potassium formate, zinc formate, magnesium formate, sodium benzoate, potassium benzoate, zinc benzoate, and magnesium benzoate, and the amount of organic pore-forming agent added is 5 wt.% of the amount of biomass raw material added.

[0042] S3, pre-carbonization treatment: pre-carbonize the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is argon, the carbonization temperature is 500° C., and the carbonization time is 6 hours.

[0043] S4, pulverizing and refining: pulverizing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 1200°C, the carbonization time is 8 hours, and the heating rate is 6°C / min; the pulverization method is air flow powder, and the carbonized material is pulverized to a D50 of 3-15μm.

[0044] S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material. Example

[0045] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crush and sieve the raw material to obtain a biomass raw material of the first fineness. Specifically, the mesh number of the sieve is ≥15 mesh, and the raw material is coconut shell, walnut shell, nut shell, apricot shell, coffee shell, corn cob, straw, reed, bamboo, rice husk, poplar, eucalyptus, pine, bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

[0046] S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet mixed with acid solution, cross-linking agent, and organic pore-forming agent, and the reaction is centrifuged, washed, and dried after temperature control to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. Specifically, the reaction temperature is 100°C, and the reaction time is 5h; the acid solution is hydrochloric acid, nitric acid, phosphoric acid, and sulfuric acid, and the amount of acid solution is 3wt.% of the amount of biomass raw material added; the cross-linking agent is polyethylene glycol, phthalic acid glycoside, malonic acid, and formaldehyde, and the amount of cross-linking agent added is 2wt.% of the amount of biomass raw material added; the organic pore-forming agent is sodium gluconate, potassium gluconate, and magnesium gluconate, and the amount of organic pore-forming agent added is 10 wt.% of the amount of biomass raw material added.

[0047] S3, pre-carbonization treatment: pre-carbonize the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 600° C., and the carbonization time is 5 hours.

[0048] S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 1400°C, the carbonization time is 3h, the heating rate is 1-15°C / min; the crushing method is double rollers, and the carbonized material is crushed to a D50 of 3-15μm.

[0049] S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material. Example

[0050] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Raw material pre-crushing: crush and sieve the raw material to obtain a biomass raw material of the first fineness. Specifically, the mesh number of the sieve is ≥15 meshes, and the raw material is poplar, eucalyptus, pine, bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

[0051] S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet mixed with acid solution, cross-linking agent, and organic pore-forming agent, and the reaction is centrifuged, washed, and dried after temperature control to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. Specifically, the reaction temperature is 160°C, and the reaction time is 7h; the acid solution is hydrochloric acid, oxalic acid, and benzoic acid, and the amount of acid solution is 3 wt.% of the amount of biomass raw material added; the cross-linking agent is polyethylene glycol, phthalic acid glycoside, and malonic acid, and the amount of cross-linking agent added is 2 wt.% of the amount of biomass raw material added; the organic pore-forming agent is sodium gluconate, potassium gluconate, magnesium gluconate, potassium benzoate, zinc benzoate, and magnesium benzoate, and the amount of organic pore-forming agent added is 12 wt.% of the amount of biomass raw material added.

[0052] S3, pre-carbonization treatment: pre-carbonize the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 900° C., and the carbonization time is 5 hours.

[0053] S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness. Specifically, the protective atmosphere is nitrogen and argon, the carbonization temperature is 1300°C, the carbonization time is 7h, and the heating rate is 5°C / min; the crushing method is jaw crushing, air flow powder, and ball milling, and the carbonized material is crushed to a D50 of 3-15μm.

[0054] S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material.

[0055] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, comprising the following steps: S1. Pre-crushing of raw materials: crushing the walnut shell raw materials and passing them through a 20-mesh sieve to obtain walnut shell raw materials of a certain fineness.

[0056] S2, raw material homogenization modification: the walnut shell raw material of a certain fineness obtained in step S1 is mixed with hydrochloric acid, polyethylene glycol crosslinking agent, sodium acetate and deionized water, and then reacted in a high-pressure reactor at 100°C for 5 hours, and then centrifuged, washed and dried to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. The addition amounts of hydrochloric acid, polyethylene glycol crosslinking agent and sodium acetate are 2.5wt.%, 2.0wt.% and 20wt.% of the walnut shell raw material addition amount, respectively.

[0057] S3, pre-carbonization treatment: the modified raw material obtained in step S2 is pre-carbonized under a nitrogen atmosphere, the carbonization temperature is 800° C., the carbonization time is 3 h, and a pre-carbonized material is obtained.

[0058] S4. Pre-carbonization treatment: crushing and refining: use a jet mill to crush and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material with a D50 of 7 μm.

[0059] S5. High-temperature carbonization: The pre-carbonized material obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a carbonization temperature of 1300° C., a carbonization time of 3 h, and a heating rate of 5° C. / min to obtain the high-capacity hard carbon negative electrode material of Application Example 1.

[0060] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0061] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material, which is different from Application Example 1 in that no acid solution is added for modification treatment, and includes the following steps: S1. Pre-crushing of raw materials: crushing the walnut shell raw materials and passing them through a 20-mesh sieve to obtain walnut shell raw materials of a certain fineness.

[0062] S2, raw material modification: the walnut shell raw material of a certain fineness obtained in step S1 is mixed with polyethylene glycol crosslinking agent, sodium acetate and deionized water, and then reacted in a high-pressure reactor at 100°C for 5 hours, and then centrifuged, washed and dried to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. The addition amounts of polyethylene glycol crosslinking agent and sodium acetate are 2.0 wt.% and 20 wt.% of the addition amount of walnut shell raw material, respectively.

[0063] S3, pre-carbonization treatment: the modified raw material obtained in step S2 is pre-carbonized under a nitrogen atmosphere, the carbonization temperature is 800° C., the carbonization time is 3 h, and a pre-carbonized material is obtained.

[0064] S4. Pre-carbonization treatment: pulverization and refinement: Use a jet mill to pulverize and refine the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material with a D50 of 7 μm.

[0065] S5. High-temperature carbonization: The pre-carbonized material obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a carbonization temperature of 1300° C., a carbonization time of 3 h, and a heating rate of 5° C. / min to obtain a hard carbon negative electrode material of comparative example 1.

[0066] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0067] This embodiment relates to a method for preparing a biomass hard carbon sodium ion battery negative electrode material, which is different from the application example 1 in that no cross-linking agent is added for modification, and comprises the following steps: S1. Pre-crushing of raw materials: crushing the walnut shell raw materials and passing them through a 20-mesh sieve to obtain walnut shell raw materials of a certain fineness.

[0068] S2, raw material modification: the walnut shell raw material of a certain fineness obtained in step S1 is mixed with hydrochloric acid, sodium acetate and deionized water, and then reacted in a high-pressure reactor at 100°C for 5 hours, and then centrifuged, washed and dried to obtain a modified raw material rich in organic pore-forming agent and uniformly distributed. The addition amounts of hydrochloric acid and sodium acetate are 2.5wt.% and 20wt.% of the addition amount of the walnut shell raw material, respectively.

[0069] S3, pre-carbonization treatment: the modified raw material obtained in step S2 is pre-carbonized under a nitrogen atmosphere, the carbonization temperature is 800° C., the carbonization time is 3 h, and a pre-carbonized material is obtained.

[0070] S4. Pre-carbonization treatment: crushing and refining: use a jet mill to crush and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material with a D50 of 7 μm.

[0071] S5. High-temperature carbonization: The pre-carbonized material obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a carbonization temperature of 1300° C., a carbonization time of 3 h, and a heating rate of 5° C. / min to obtain the hard carbon negative electrode material of comparative example 2.

[0072] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) was used as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0073] The results of nitrogen adsorption and desorption tests show that the specific surface areas of Example 1, Comparative Example 1 and Comparative Example 2 are 4.8, 25.4 and 18.9 m2 / g, respectively. The synergistic effect of the acid solution, cross-linking agent and organic pore-forming agent makes the hard carbon material almost free of mesopores and macropores. The closure of the micropores in the subsequent high-temperature sintering process makes the material have a lower specific surface area.

[0074] The He gas true density test results show that the true densities of Example 1, Comparative Example 1 and Comparative Example 2 are 1.86, 1.93 and 1.97 g / cm3 respectively, indicating that the synergistic effect of the acid solution, cross-linking agent and organic pore-forming agent forms a rich microporous structure inside the hard carbon material, thereby reducing the true density of the hard carbon material.

[0075] The constant current charge and discharge test measured that the first-week charging specific capacity of Example 1, Comparative Example 1 and Comparative Example 2 were 342, 276 and 281 mAh / g, respectively, and the first-week coulombic efficiency were 92.1, 86.7 and 88.4%, respectively, indicating that the formation of a rich microporous structure inside the hard carbon material can effectively improve the sodium storage capacity of the hard carbon material, and reducing the specific surface area of ​​the material can effectively improve the first-week coulombic efficiency of the hard carbon material.

[0076] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency, characterized in that The following steps are involved: S1. Raw material pre-crushing: crushing and sieving the raw material to obtain a biomass raw material of the first fineness; S2, raw material homogenization modification: the biomass raw material obtained in step S1 is wet-mixed with acid solution, cross-linking agent and organic pore-forming agent, centrifuged, washed and dried after temperature-controlled reaction to obtain a modified raw material rich in organic pore-forming agent evenly distributed; S3, pre-carbonization treatment: pre-carbonizing the modified raw material obtained in step S2 under a protective atmosphere to obtain a pre-carbonized material; S4, crushing and refining: crushing and refining the pre-carbonized material obtained in step S3 to obtain a pre-carbonized material of the second fineness; S5, high temperature carbonization: the pre-carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain the final hard carbon sodium ion battery negative electrode material.

2. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S2, the reaction temperature is 60-200°C, and the reaction time is 3-10h.

3. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S2, the acid solution is one or more of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, formic acid, acetic acid, citric acid, oxalic acid and benzoic acid; the amount of the acid solution is 0.5-10 wt.% of the amount of biomass raw material added.

4. The method for preparing a biomass hard carbon sodium ion battery negative electrode material with good consistency according to claim 5, characterized in that: In step S2, the cross-linking agent is one or more of polyethylene glycol, phthalic acid glycosides, malonic acid, formaldehyde, benzaldehyde, propylenediamine, glyoxal, terephthalaldehyde, urea-formaldehyde, furfural, diaminodiphenylmethane, m-xyleneamine, and diammonium biphenyl; the added amount of the cross-linking agent is 1-5wt.% of the added amount of the biomass raw material.

5. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S2, the organic pore-forming agent is one or more of sodium gluconate, potassium gluconate, magnesium gluconate, zinc gluconate, sodium acetate, potassium acetate, zinc acetate, magnesium acetate, sodium citrate, potassium citrate, zinc citrate, magnesium citrate, sodium oxalate, potassium oxalate, zinc oxalate, magnesium oxalate, sodium formate, potassium formate, zinc formate, magnesium formate, sodium benzoate, potassium benzoate, zinc benzoate, and magnesium benzoate; the amount of the organic pore-forming agent added is 5-50 wt.% of the amount of biomass raw material added.

6. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S3, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 500-1000°C, and the carbonization time is 2-6h.

7. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S4, the protective atmosphere is nitrogen and / or argon, the carbonization temperature is 1200-1500°C, the carbonization time is 2-8h, and the heating rate is 1-15°C / min.

8. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 9, characterized in that: In step S1, the mesh number of the sieve is ≥15 meshes.

9. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S4, the pulverizing method is one or more of the following: roller mill, mechanical mill, Raymond mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the carbonized material is pulverized until its D50 is 3-15 μm.

10. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with good consistency according to claim 1, characterized in that: In step S1, the raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, corn cob, straw, reed, bamboo, rice husk, poplar, eucalyptus, pine, bagasse, starch, cassava flour, fruit wood, miscellaneous wood, fir, and oak.

Citation Information

Patent Citations

  • Bamboo-based hard carbon active electrode material, preparation thereof and application of bamboo-based hard carbon active electrode material in sodium ion battery

    CN115849333A

  • Hard carbon negative electrode material, preparation method and application thereof, and battery

    CN116002659A

  • Preparation method of homogeneous spherical hard carbon negative electrode material

    CN116395665A

  • Preparation method of high-yield biomass-based sodium ion battery hard carbon negative electrode material

    CN118343735A

  • Preparation method and application of lignin-based resin and carbon material for battery

    CN118405685A

Cited By

  • Biomass-based sodium-ion battery hard carbon material as well as preparation method and application thereof

    CN120664526A

  • Biomass-based sodium-ion battery hard carbon materials, their preparation methods and applications

    CN120664526B

  • Coal pitch-based sodium battery negative electrode material and sodium ion battery

    CN120809768A

  • Multi-carbon-source applicable green synthesis method for preparing supercapacitor porous carbon through one-pot one-time carbonization process

    CN121306816A